2016
DOI: 10.3847/0004-637x/829/2/133
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Rotation Measure Synthesis of Intermediate Redshift Quasars as a Probe of Intervening Matter

Abstract: There is evidence that magnetized material along the line of sight to distant quasars is detectable in the polarization properties of the background sources. The polarization properties appear to be correlated with the presence of intervening MgII absorption, which is thought to arise in outflowing material from star forming galaxies. In order to investigate this further, we have obtained high spectral resolution polarization measurements, with the VLA and ATCA, of a set of 49 unresolved quasars for which we h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 41 publications
1
50
1
1
Order By: Relevance
“…Robishaw et al (2008) detected field strengths up to 18 mG in starburst galaxies but ordered galactic magnetic fields in the ISM are typically expected to be of the order of several µG, similar in strength to the fluctuating components. Kim et al (2016) found in intermediate redshift galaxies a clear correlation between large magnetic field strength and Mg II absorption, which indicates a link between strong outflows and a high magnetisation, as well as field as strong as a few 10 −6 G at epochs as early as z 4 − 5.…”
Section: Introductionmentioning
confidence: 83%
“…Robishaw et al (2008) detected field strengths up to 18 mG in starburst galaxies but ordered galactic magnetic fields in the ISM are typically expected to be of the order of several µG, similar in strength to the fluctuating components. Kim et al (2016) found in intermediate redshift galaxies a clear correlation between large magnetic field strength and Mg II absorption, which indicates a link between strong outflows and a high magnetisation, as well as field as strong as a few 10 −6 G at epochs as early as z 4 − 5.…”
Section: Introductionmentioning
confidence: 83%
“…Apart from the RRM measurement for these quasars sightlines, their observed fractional polarisation (p) is another parameter which might also be a useful tool to probe the magnetic field in the intervening galaxies, again by comparing p values and its correlation with RRM for subsample with and without Mg ii absorbers. Many past studies have explored this possibility and found that indeed higher RRM is associated with the lesser p value (Hammond et al 2012;Bernet et al 2013;Kim et al 2016). For instance, Hammond et al (2012) found an anti-correlation between RRM and fractional polarization.…”
Section: Introductionmentioning
confidence: 97%
“…All RM synthesis calculations were performed using the pyrmsynth package. 4 We made use of Astropy, NumPy, matplotlib and joblib in preparing this manuscript.…”
Section: Acknowledgmentsmentioning
confidence: 99%